Electrospray ion beam deposition and preparation of model molecular solar cells surfaces - Alharbi, Nouf (2023)
Studying the fundamental science of surface science of dye sensitised solar cells requires placing complex molecules on surfaces in an ultra-high vacuum. Since most dye molecules are fragile and non-volatile to be deposited by thermal evaporation or sublimation technique, electrospray deposition was therefore explored as an alternative method. This thesis aims to work on developing the electrospray deposition technique to obtain high-quality monolayers in situ in high vacuum environments.